Preschool teachers’ psychological wellbeing, emotion regulation, and emotional responsiveness: a US-Korea comparison - Byun, Sooyeon; Jeon, Lieny (Frontiers in Psychology, 2023)
Introduction Psychological wellbeing is an essential indicator of early care and education (ECE) teachers’ positive practices across countries. Moreover, previous studies suggest that teachers’ wellbeing and practice may be indirectly associated via emotion regulation. However, teachers in various contexts demonstrate different patterns of psychological wellbeing, emotion regulation, and emotional responsiveness, and the ways these factors associate with each other also vary. Methods The current study investigates whether the indirect associations between ECE teachers’ psychological wellbeing (i.e., emotional exhaustion, job-related competence, and personal stress) and their responsiveness toward children’s emotions via emotion regulation (i.e., reappraisal and suppression) appear differently in two national contexts, the United States (US) and South Korea (SK). Multi-group path analysis was conducted to compare the mediation models between US teachers (n = 1,129) and SK teachers (n = 322). Results We found significant indirect associations among wellbeing, emotion regulation, and responsiveness in both countries. However, significant associations were more prominent among SK teachers, and the patterns of indirect associations had substantial cross-country differences. Furthermore, the roles of reappraisal and suppression emotion regulation found to be different among ECE teachers in SK and US. Discussion The cross-country variations in the associations among wellbeing, emotion regulation, and responsiveness suggest that differential policy efforts and intervention strategies are needed for ECE teachers in the US and SK.